(untitled) (Experimental biology, 2016)
Has been held the comparative agro ecological characterization of complex physiological and biochemical parameters in growing 16th cultivars and of 77 variety samples of barley under different conditions of salinity (0.5-2% NaCl). Found that the physiological biotests (weight of seedlings, the length of the primary root system and length of coleoptile) and biochemical biotest (coefficient of tolerance to salt by the activity of free proline in the leaves of seedlings barley) are the most indicative tests of tolerance to salt. These tests reliably differentiate samples on salt-tolerant and salt sensitive samples of barley compared with other laboratory methods; in addition, these methods reduce the time to identify sustainable models for genetic and breeding research. Found a six variety samples of barley (59 87-2K, 9-95-2K, 89/83-4, 27/6.8, 3/24-01 and 164 99-4) and one a cultivar of barley of Syr-Arua which are resistance to salinity.